Internal transcribed spacer 2 barcode: a good tool for identifying Acanthopanacis cortex - Zhao, Sha; Chen, Xiaochen; Song, Jingyuan; Pang, Xiaohui; Chen, Shilin (Frontiers in Plant Science, 2015)
Acanthopanacis cortex has been used in clinical applications for a long time. Considering some historical and geographical factors, Acanthopanacis cortex is easily confused with other herbs in medicine markets, thereby causing potential safety issues. In this study, we used the internal transcribed spacer 2 (ITS2) barcode to identify 69 samples belonging to six species, including Acanthopanacis cortex and its adulterants. The nearest distance, single-nucleotide polymorphisms (SNPs), and neighbor-joining (NJ) tree methods were used to evaluate the identification ability of the ITS2 barcode. According to the kimura-2-parameter model, the intraspecific distance of Eleutherococcus nodiflorus ITS2 sequences ranged from 0 to 0.0132. The minimum interspecific distance between E. nodiflorus and E. giraldii was 0.0221, which was larger than the maximum intraspecific distance of E. nodiflorus. Three stable SNPs in ITS2 can be used to distinguish Acanthopanacis cortex and its closely related species. The NJ tree indicated that the Acanthopanacis cortex samples clustered into one clade, which can be distinguished clearly from the adulterants of this herb. A secondary structure of ITS2 provided another dimensionality to identify species. In conclusion, the ITS2 barcode effectively identifies Acanthopanacis cortex, and DNA barcoding is a convenient tool for medicine market supervision.